Nicotine Reduction Revisited: Science and Future Directions - Hatsukami, Dorothy K. (Tob Control, 2010)
Regulation of nicotine levels in cigarettes and other tobacco products is now possible with the passage of the Family Smoking Prevention and Tobacco Control Act (FSPTCA) in 2009 giving the U.S. Food and Drug Administration authority to regulate tobacco products, and with Articles 9-11 of the World Health Organization Framework Convention on Tobacco Control.[1-2] Both regulatory approaches allow establishing product standards for tobacco constituents, including nicotine. The FSPTCA does not allow nicotine levels to be decreased to zero, although FDA has the authority to reduce nicotine yields to very low, presumably non-addicting levels. The proposal to reduce levels of nicotine to a level that is non-addicting was originally suggested in 1994.[3] Reduction of nicotine in tobacco products could potentially have a profound impact on reducing tobacco-related morbidity and mortality. To examine this issue, two meetings were convened in the United States with non-tobacco-industry scientists of varied disciplines, tobacco control policy-makers and representatives of government agencies. This article provides an overview of the current science in the area of reduced nicotine content cigarettes and key conclusions and recommendations for research and policy that emerged from the deliberations of the meeting members.